A transgressão do corpo nu na fotografia: o retorno dos corpos decadentes (Revista da Universidade Federal de Minas Gerais, 2012)
Nowadays the imposition of an ideal body model, linked to the pattern of classical art, has intensified and called critical attention for its impact on society. This article presents the works of Joel-Peter Witkin and Jan Saudek, photographers who challenge a model of beauty that does not accept the decay of the body and deny the nearness of death. Through their work, they contribute to weaken the hegemony of this apollonian discourse and promote the visibility of other body models.